Social Interaction and Technology Adoption: Experimental Evidence from Improved Cookstoves in Mali - Jacopo Bonan; Pietro Battiston; Jaimie Bleck; Philippe LeMay-Boucher; Stefano Pareglio; Bassirou Sarr; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2017)
We investigate the role of social interaction in technology adoption by conducting a field experiment in neighborhoods of Bamako. We invited women to attend a training/marketing session, where information on a more efficient cooking stove was provided and the chance to purchase the product at market price was offered. We randomly provided an information nudge on a peer's willingness to buy an improved cookstove. We find that women purchase and use the product more when they receive information on a peer who purchased (or previously owned) the product, particularly if she is viewed as respected. In general, we find positive direct and spillover effects of attending the session. We also investigate whether social interaction plays a role in technology diffusion. We find that women who participated in the session, but did not buy during the intervention, are more likely to adopt the product when more women living around them own it. We investigate the mechanisms and provide evidence supporting imitation effects, rather than social learning or constraint interaction.
Keywords: D03; M31; O13; O33; 330; Technology Adoption; Social Interaction; Cookstoves; Mali